The Sociopathic Behaviour In Gone Girl - Krisandy Henry (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
Gone Girl tells the story of a woman named Amy Elliott Dunne, a woman who wants to have a perfect marriage like in a book Amazing Amy. However, real life is different from her expectation. Her husband has an affair with his student. It pushes her to do some controlling acts to manifest her wish about perfect marriage. And that is the time when Amy shows her personality as a sociopath. To know more about Amy, this study focuses on the cause and the trigger of Amy’s sociopath and to identify the characteristics of Amy’s sociopath through her actions and the ways she thinks. There are two results for this research. The first one is Amy shows four out of seven characteristics of antisocial personality disorder. There are failure to conform to social, deceitfulness, reckless disregard for safety, and lack of remorse. Amy is a person with sociopathic behaviour that is portrayed through her actions, such as lying, manipulating, even killing other in order to get what she wants. The second one is Amy’s sociopath is caused by her parents that always give pressure to her and Amy’s husband affair triggers her sociopathic behaviour. It is clear that people with antisocial personality disorder have different characteristics with normal people.  The way they think and solve the problems are different from normal people. Keywords: Antisocial personality disorder, Sociopath, Pressure